Exhaled breath barbotage: A new method of pulmonary surfactant dysfunction assessing - Mizev, Aleksey; Shmyrova, Anastasia; Mizeva, Irina; Pshenichnikova-Peleneva, Irina (Journal of aerosol science, 2018)
Exhaled air contains submicron droplets of alveolar lining fluid (ALF), which are generated in the small airways of human lungs and are in fact ALF micro-samples. The trapping of these droplets makes it possible to collect a native material from respiratory tract in a non-invasive manner, which holds great promise for lung diagnostics. In this work, we present an aerosol droplet sampling technique based on the exhaled breath barbotage (EBB) procedure. The proposed technique offers a unique opportunity to accumulate pulmonary surfactant (PS), a major constituent of ALF, on a liquid surface. The Wilhelmy plate method was used to measure the variation of the surface pressure over the surface area for the EBB samples collected in a Langmuir trough. A data processing algorithm was derived to evaluate the surface pressure (π) – surface concentration (Γ) isotherm from the raw data. With this algorithm, one can restore the isotherm even in the case when the amount of surfactant adsorbed on the surface is unknown. The (π−Γ) isotherms found for the samples collected in the groups of healthy volunteers and patients with pulmonary tuberculosis were compared with the isotherms obtained for artificial PS. It has been established that the isotherms measured for healthy people and artificial surfactant coincide, and the isotherms obtained in the TB group have lower inclination, which is indicative of a lower surface activity. The EBB method developed in this study can be used as a diagnostic tool for assessment of the functional status of PS in screening tests and subsequent treatment. •Exhaled breath barbotage (EBB) is a new method to trap out aerosol droplets from exhaled air.•Pulmonary surfactant (PS) accumulates on free liquid surface during EBB procedure.•Surface properties of PS of healthy and TB subjects were measured in Langmuir trough.•TB patients demonstrate lower surface activity of PS in comparison with control group and artificial PS.•The proposed technique has high potential for assessing PS dysfunction.